Biological treatment of Pb and Zn using sequencing batch reactor - Omar Syah Jehan Elham,; Siti Afifah Muda,; Hassimi Abu Hasan,; Siti Rozaimah Sheikh Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Effective wastewater treatment is essential to prevent water resources from being polluted. Usually, wastewater treatment can be divided into three distinct types; physical, chemical and biological treatment. This research aims to biologically treat Pb and Zn using the Sequencing Batch Reactor (SBR) system. There were four stages involved in the operation of SBR, which include; filled, react, settle and draw. The dissolved oxygen (DO) was controlled in the range of 2-5 mg/L, while the pH was maintained at the range of pH 6.5-7.5. Synthetic wastewater was used as influent with a C:N ratio of 200:40. In total, there were three HRT’s tested, which were 8, 24 and 48 hrs respectively. Additionally, the water quality parameters analysed were (chemical oxygen demand) COD, ammonium, mixed liquor suspended solid (MLSS) and heavy metal Pb and Zn in the effluent. The average percentage of COD removals in this research was 66.0% while the average heavy metal removal for Pb and Zn were 97.1% and 94.7%, respectively. Therefore, based on the three hydraulic retention times, (HRT’s), HRT 48 showed the highest performance in removing Pb and Zn.